2010
DOI: 10.1002/mrm.22313
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic nanoparticles for imaging dendritic cells

Abstract: We report the development of superparamagnetic iron oxide (SPIOs) nanoparticles and investigate the migration of SPIO-labeled dendritic cells (DCs) in a syngeneic mouse model using magnetic resonance (MR) imaging. The size of the dextran-coated SPIO is roughly 30 nm, and the DCs are capable of independent uptake of these particles, although not at levels comparable to particle uptake in the presence of a transfecting reagent. On average, with the assistance of polylysine, the particles were efficiently deliver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 17 publications
0
46
0
Order By: Relevance
“…Quantitative analysis has shown that DC can independently take up about 10 pg Fe/cell 8 , and uptake can be as high as 35 pg Fe/cell with the use of a transfection agent 55 . Transfection agents are chemical-based delivery molecules that act to enhance the uptake of nanoparticles into the cell.…”
Section: Volume 5 September/october 2013mentioning
confidence: 99%
“…Quantitative analysis has shown that DC can independently take up about 10 pg Fe/cell 8 , and uptake can be as high as 35 pg Fe/cell with the use of a transfection agent 55 . Transfection agents are chemical-based delivery molecules that act to enhance the uptake of nanoparticles into the cell.…”
Section: Volume 5 September/october 2013mentioning
confidence: 99%
“…[3][4][5] Iron oxide particles may also be used for noninvasive tracking of the migration and biodistribution of immune cells. 6 Cellular tracking typically involves labeling the cells ex vivo and subsequently implanting [7][8][9][10] or systemically 11 administering particles into the living body. These labeling methods are useful for observing the migration of immune cells toward a target, such as a tumor, and their subsequent accumulation.…”
Section: Introductionmentioning
confidence: 99%
“…8,25,26 Briefly, the BM cells from mouse femurs and tibias were flushed out with RPMI 1640 medium using a 27-gauge needle and collected into a 50 mL conical tube after they are passed through a nylon mesh cell strainer of 70 µm pore size. Red blood cells were lysed from the BM cells by incubation for 3 minutes in 0.83% ammonium chloride at RT.…”
Section: Preparation Of Bone Marrow-derived Dcs (Bmdcs)mentioning
confidence: 99%
“…25 In brief, the tissue sections were treated with 3% hydrogen peroxide to quench the endogenous peroxidases, followed by ultra V block (Lab Vision, Fremont, CA, USA) for 5 minutes before the addition of primary antibody. The sections were incubated with affinity-purified hamster anti-CD11c antibody (eBioscience) at 1:200 dilution for 1 hour at RT, washed in PBS ×3, incubated with biotin-conjugated secondary antibody for 1 hour, followed by treatment with the Vectastain ABC Elite kit (Vector Laboratories, Burlingame, CA, USA) and DAB (Dako, Carpinteria, CA, USA).…”
Section: Histological Analysis Of the Migration To The Lymph Nodes (Lns)mentioning
confidence: 99%